2013
DOI: 10.1007/s10964-013-9905-9
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Disparities of Hazardous Drinking Between Sexual Minority and Heterosexual Individuals from Adolescence to Young Adulthood

Abstract: Sexual minority (lesbian and gay, bisexual, mostly heterosexual) individuals are at an increased risk for hazardous drinking than heterosexual individuals, but little is known about the nature of the disparities as adolescents reach adulthood. We used four waves of a nationally representative data set, the National Longitudinal Study of Adolescent Health (Add Health), to examine disparities of hazardous drinking outcomes between sexual minority and heterosexual men and women from adolescence to young adulthood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
95
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(102 citation statements)
references
References 39 publications
6
95
1
Order By: Relevance
“…Thus, the orientation dimension used in our study seems adequate to address our research question and this approach has also been adopted in previous studies [3,5,29]. Sexual orientation has been found to be fluid over time [59][60][61]; however, in ALSPAC, it was recorded only at age 15, so we were unable to assess change.…”
Section: Mean (Sd) Mean (Sd)mentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the orientation dimension used in our study seems adequate to address our research question and this approach has also been adopted in previous studies [3,5,29]. Sexual orientation has been found to be fluid over time [59][60][61]; however, in ALSPAC, it was recorded only at age 15, so we were unable to assess change.…”
Section: Mean (Sd) Mean (Sd)mentioning
confidence: 99%
“…Rates of hazardous drinking are high among sexual minority adolescents and persist into adulthood [3,5,6,8,29]. Thus, it is important to study the aetiology of alcohol problem use within this at-risk group to inform the development of targeted effective interventions and policies.…”
Section: Introductionmentioning
confidence: 99%
“…A limited number of studies have examined age trends in substance use disparities to date. One longitudinal study found that the disparity in heavy drinking among SMs adolescents increased into young adulthood (Dermody et al, 2014); another found that SM reported higher initial rates of substance use and more rapid escalation of use compared to their heterosexual peers (Marshal et al, 2009). Similarly, a study of college students found that young men who have sex with men had alcohol use trajectories that escalated more rapidly than heterosexual young men (Hatzenbuehler et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to health consequences, there are numerous negative social and personal consequences of substance use including impaired interpersonal relationships, addiction, impaired cognitive functioning, decreased productivity, and drug-induced death (Bouchery, Harwood, Sacks, Simon, & Brewer, 2011;Griffin, Bang, & Botvin, 2010). A large body of work has demonstrated that compared to heterosexual women, sexual minority women (SMW: lesbians or bisexuals, women who partner with women, and women who have sex with women) have elevated rates of substance use morbidity (Bloomfield, Wicki, Wilsnack, Hughes, & Gmel, 2011;Dermody et al, 2013;Drabble, Trocki, Hughes, Korcha, & Lown, 2013;McCabe, West, Hughes, & Boyd, 2013). For example, McCabe, Hughes, Bostwick, West, & Boyd (2009) examined substance use disorder prevalence rates based on sexual orientation in a nationally representative sample of women.…”
Section: Introductionmentioning
confidence: 99%